Patterns of response and progression in bone and soft tissue during and after treatment with radium‐223 for metastatic castrate‐resistant prostate cancer. Issue 10 (2nd May 2019) - McNamara, Megan Ann; Oyekunle, Taofik; Chin, Bennett B.; Oldan, Jorge; Anand, Aseem; Ritz, Michala; Shantzer, Lindsey; Anand, Monika; Armstrong, Andrew J.; George, Daniel J.
Abstract: Background: Radium‐223 improves survival and time to first symptomatic skeletal event in symptomatic bone predominant metastatic castrate‐resistant prostate cancer (mCRPC). The imaging response to radium‐223 has not been well characterized. Methods: To describe patterns of response and progression with radium‐223, we performed a retrospective review of all mCPRC patients who received radium‐223 at Duke from 1 June 2013 to 1 June 2015. Radionuclide bone scans obtained at baseline, during, and after treatment were reviewed by two radiologists. The automated bone scan index (aBSI) was generated at each time point using EXINI bone BSI version 2.4. Computed tomography (CT) and magnetic resonance imaging (MRI) clinical radiology reports were reviewed to evaluate for soft tissue, visceral, epidural, and bone progression. Clinical data were abstracted from the electronic health record. Results: We identified 61 men who received at least one dose of radium‐223 at Duke during the study period (median, 5 doses; range, 1‐6). Among men with imaging during treatment, 2 of 14 (14.3%) had resolution of greater than or equal to 1 lesion on bone scan, 4 of 14 (28.6%) had zero new bone lesions, 10 of 14 (71.4%) had greater than or equal to 1 new bone lesion, 14 of 26 (53.9%) progressed on CT. After radium‐223, 6 of 39 (15.4%) had resolution of 1 to 4 bone lesions, 15 of 39 (38.5%) demonstrated zero new bone lesions, 24 of 39 (61.5%) progressed on bone scan, 15 of 37 (40.5%) progressed on CT, and 10 of 34 (29.4%) progressed on both bone scan and CT. No men with zero new bone lesions after radium‐223 ultimately progressed in bone alone and only 3 of 15 eventually demonstrated any progression in the bone. aBSI decreased significantly from baseline to after radium‐223 among men with zero new bone lesions (median change in aBSI −0.23 [IQR, −1.5, 0.02]) and increased significantly for men with greater than or equal to 1 new postradium bone lesions (median change in aBSI 1.41 [IQR, −0.05, 3.63] [ P = 0.018]). Conclusions: Bone and soft tissue progression during and following radium‐223 is common in heavily pretreated men with mCRPC. However, stable disease and responses were observed in a subset of patients and may be associated with durable treatment response in the bone. Prospective studies are needed to further investigate the change in aBSI as a biomarker of bone scan response/stabilization and progression following treatment with radium‐223.